Increase Student Activity Through The Use of Interactive Learning Videos in Civics Learning during the Study From Home - Puteri, Dwi Ane Risqi; Ibrahim, Nurdin; Priyono (LPPM Undiksha, 2023)
The Civics learning process should be carried out interactively by choosing media to actively stimulate students to solve contextual problems. But the problem is that the learning process must focus on students. This study aimed to conduct a needs analysis to develop interactive learning videos for Civics subjects. This research was conducted using the R&D (Research & Development) method. The research subjects were eleventh-grade students, totaling 36 students—data collection methods by observation, interviews, and tests. In learning from home, students want media in the form of interactive learning videos. Interactive learning videos can be used for a more learner-centered learning process because they contain questions. The questions in the learning video are expected to make students actively listen and answer the learning material. From the analysis results, it was concluded that interactive learning videos are needed to help the learning process be more student-centered to have a positive impact, especially in creating an interactive learning process.